Environmental engineering - Kiely, Gerard (Boston, Massachusetts : Irwin Inc., 1996)
This text successfully integrates engineering and ecological concepts and provides a comprehensive introduction to mathematical modeling of air and water pollution problems. It also includes key chapters on environmental management and numerous worked examples and end-of-chapter exercises.
Keywords: ENVIRONMENTAL ENGINEERING